2019
DOI: 10.1186/s13041-019-0461-4
|View full text |Cite
|
Sign up to set email alerts
|

Segregated expressions of autism risk genes Cdh11 and Cdh9 in autism-relevant regions of developing cerebellum

Abstract: Results of recent genome-wide association studies (GWAS) and whole genome sequencing (WGS) highlighted type II cadherins as risk genes for autism spectrum disorders (ASD). To determine whether these cadherins may be linked to the morphogenesis of ASD-relevant brain regions, in situ hybridization (ISH) experiments were carried out to examine the mRNA expression profiles of two ASD-associated cadherins, Cdh9 and Cdh11, in the developing cerebellum. During the first postnatal week, both Cdh9 and Cdh11 were expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 88 publications
3
16
0
Order By: Relevance
“…It is likely that cadherins, Cdh11 in particular, may play important roles in mediating synapse formation during the wiring of circuits in these brain areas. Consistent with this postulation, our recent work showed Cdh11 expression in ASD-associated sub-regions in the CB of developing mouse brain 58 .…”
Section: Multiple Members Of the Cadherin Family As Risk Factors For Asdsupporting
confidence: 79%
“…It is likely that cadherins, Cdh11 in particular, may play important roles in mediating synapse formation during the wiring of circuits in these brain areas. Consistent with this postulation, our recent work showed Cdh11 expression in ASD-associated sub-regions in the CB of developing mouse brain 58 .…”
Section: Multiple Members Of the Cadherin Family As Risk Factors For Asdsupporting
confidence: 79%
“…In the past few years, advanced studies conducted using modern genetic and neuroimaging methods, such as functional magnetic resonance imaging (fMRI) have indicated that human cerebellum also sustains autonomic, limbic, and cognitive functions, including language and thinking; hence, this brain region was lately associated with the occurrence and development of autism . On the basis of the data collected by genetic testing and/or using MRI methods, other reports also relate cerebellar dysfunctions to Alzheimer disease (AD), attention‐deficit/hyperactivity disorder, Huntington disease, hereditary ataxia, and Parkinson disease (PD) .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA322 (paired with protogenin Prtg) is associated with apoptosis and Alzheimer's disease (AD) [67]. Finally, Mir100 (paired with cadherin Cdh9), is associated with neurological disorders such as AD, schizophrenia and autism [68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%